2022
DOI: 10.1002/lary.30524
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Macrophage Population in Patients With Idiopathic Subglottic Stenosis

Abstract: ObjectivesIdiopathic subglottic stenosis (iSGS) is characterized by progressive fibrosis and subglottic luminal narrowing. Currently, immune characterization has focused on T‐cells; however, macrophages remain largely unexplored. The goals of this study are to characterize the transcriptome of iSGS macrophages and the fibrogenic nature of identifed biomarkers.Study DesignBioinformatics and in vitro.MethodsHuman tracheal biopsies from iSGS scar (n = 4), and matched non‐scar (n = 4) regions were analyzed using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The role of IL‐17A implicates the involvement of myeloid cells, such as monocytes, in the iSGS inflammatory/immune response. Ospino et al demonstrate an increase in cells that are CD11b+ (macrophages) that also express the proinflammatory protein S100A8/A9 in human iSGS tracheal samples when compared to healthy controls 18 . Similarly a study using the murine SGS model found increased levels of dysregulated macrophages, specifically M2 macrophages, in the murine stenotic tracheal samples.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The role of IL‐17A implicates the involvement of myeloid cells, such as monocytes, in the iSGS inflammatory/immune response. Ospino et al demonstrate an increase in cells that are CD11b+ (macrophages) that also express the proinflammatory protein S100A8/A9 in human iSGS tracheal samples when compared to healthy controls 18 . Similarly a study using the murine SGS model found increased levels of dysregulated macrophages, specifically M2 macrophages, in the murine stenotic tracheal samples.…”
Section: Discussionmentioning
confidence: 95%
“…that are CD11b+ (macrophages) that also express the proinflammatory protein S100A8/A9 in human iSGS tracheal samples when compared to healthy controls. 18 Similarly a study using the murine SGS model found increased levels of dysregulated macrophages, specifically M2 macrophages, in the murine stenotic tracheal samples. This was demonstrated by increased gene expression of the M2 marker Arg1 in SGS mice compared to normal controls.…”
mentioning
confidence: 95%
“…The application of newly developed methods such as single cell RNA sequencing (scRNAseq) provides important insights into the prevailing cellular and transcriptional situation of multiple pathologies (12). Using this method, research groups have decoded the pathologic airway epithelium of ISGS and identified S100A8/A9 as a key biomarker of ISGS macrophages (12)(13)(14). Fibrotic diseases are typically driven by multiple different cell types, with fibroblasts assuming a crucial role as the primary producers of the ECM in most cases (15).…”
Section: Introductionmentioning
confidence: 99%